Development of a Restitution Model in Optimizing Legal Protection for Victims of Human Trafficking in Indonesia - Angkasa Angkasa; Rani Hendriana; Filep Wamafma; Ogiandhafiz Juanda; Bhanu Prakash Nunna (Journal of Indonesian Legal Studies, 2023)
This study aims to develop a model for the effective implementation of restitution criminal sanctions against individuals involved in trafficking in persons. The findings of this research hold strategic significance in terms of providing legal protection to victims and enhancing the concept of restitution. The study focuses on evaluating the effectiveness of imposing restitution sanctions on traffickers through judicial decisions in Indonesia. By employing a sociological juridical approach, this research examines legal norms and court rulings pertaining to prosecutors' charges against individuals involved in trafficking crimes. The analysis of these judicial decisions reveals that out of the cases reviewed, only seven included restitution sanctions, and none of the perpetrators fulfilled their restitution obligations. Instead, the offenders prioritized serving prison sentences over compensating the victims. Consequently, it is essential for prosecutors to prioritize the prosecution of perpetrators under the Law on the Eradication of Criminal Acts of Individuals. Furthermore, judges should consider utilizing the Law on the Eradication of Non-Criminal Persons and emphasizing imprisonment as an alternative to restitution.